2002
DOI: 10.1006/dbio.2002.0692
|View full text |Cite
|
Sign up to set email alerts
|

Downstream Targets of let-60 Ras in Caenorhabditis elegans

Abstract: In Caenorhabditis elegans, let-60 Ras controls many cellular processes, such as differentiation of vulval epithelial cells, function of chemosensory neurons, and meiotic progression in the germ line. Although much is known about the let-60 Ras signaling pathway, relatively little is understood about the target genes induced by let-60 Ras signaling that carry out terminal effector functions leading to morphological change. We have used DNA microarrays to identify 708 genes that change expression in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…For these 2430 genes, we employed a two-way mixed-model ANOVA as implemented by SAS to identify 1984 genes with different kinetics between the dauer exit and L1 starvation timecourses (P<0.05) (Romagnolo et al, 2002). We used a self-organizing map to cluster the 1984 genes of the dauer-specific data set into 45 nodes using 15 million iterations with Cluster software (Eisen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For these 2430 genes, we employed a two-way mixed-model ANOVA as implemented by SAS to identify 1984 genes with different kinetics between the dauer exit and L1 starvation timecourses (P<0.05) (Romagnolo et al, 2002). We used a self-organizing map to cluster the 1984 genes of the dauer-specific data set into 45 nodes using 15 million iterations with Cluster software (Eisen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the administration of exogenous compounds to C. elegans is more simplistic since worms can be soaked in drug solution, or grown on agar plates with a defined drug concentration. Gene expression studies made with disease models have revealed different transcription profiles for certain genes [28,30]. This is the kind of data that should be further investigated in order to discover new therapeutic targets.…”
Section: Future Directionsmentioning
confidence: 97%
“…An example of such an approach was taken by Romagnolo and colleagues [30], who produced transgenic overexpressing animals with constitutively active let-60(G12V) using a heat shock promoter to control transgene expression. LET-60 is the worm ortholog of Ras which is an important molecular switch that controls many developmental processes including tumour growth and neuronal differentiation.…”
Section: Disease Gene Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among many examples, microarrays have been used to examine C. elegans gene expression at various stages of development [64][65][66], in both sexes to identify male and female germline-specific transcripts [67], in animals that differ in the number of a particular structure such as male tail rays [68], in animals that have been differentially treated with ethanol [69], and in animals that have activated or overexpressed transcription factors to identify downstream target genes [70,71]. In addition to isolating RNA from a staged population of animals, techniques have been developed for isolating RNA from single tissues or cell types.…”
Section: Genomic Approaches Can Reveal Global Gene Expression Patternsmentioning
confidence: 99%